THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION, FAMILY ENVIRONMENT, AND SELF-EFFICACY ON ENTREPRENEURSHIP INTENTION OF EDUCATION STUDENTS - Zaqia Izzah Salsabila; Choirul Nikmah (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
Too many graduates coming out of teacher-training universities, far more than the education sector especially schools can ever hire, means a large portion end up jobless, which pushes the unemployment rate higher. What drives these graduates toward entrepreneurial careers guided a study looking into both internal and external factors, namely entrepreneurship education, family environment, and self-efficacy. Using a quantitative design and PLS-SEM analysis, the research gathered data from 130 students who had completed both entrepreneurship courses and internships, selected through proportionate stratified random sampling. Findings showed self-efficacy as the strongest predictor of entrepreneurial intention. Family environment shaped both self-efficacy and entrepreneurial intention in meaningful ways. Entrepreneurship education did boost self-efficacy significantly, yet its direct effect on entrepreneurial intention remained negligible. A key lesson emerges from these results, namely that mastering academic content alone will not turn into career action unless self-efficacy rises substantially. For universities, this signals a need to redesign curricula, not just chasing theoretical command but actively building psychological strength and tightening the link between classroom learning and family backing. ABSTRAK Banyaknya lulusan dari universitas kependidikan yang melebihi kapasitas serapan sektor pendidikan, khususnya sekolah, menyebabkan peningkatan angka pengangguran. Penelitian ini bertujuan untuk menginvestigasi faktor internal dan eksternal yang mendorong para lulusan tersebut menuju karier kewirausahaan, dengan fokus spesifik pada pendidikan kewirausahaan, lingkungan keluarga, dan efikasi diri. Menggunakan desain kuantitatif dan analisis PLS-SEM, penelitian ini mengumpulkan data dari 130 mahasiswa yang telah menyelesaikan mata kuliah kewirausahaan dan magang, yang dipilih melalui teknik proportionate stratified random sampling. Temuan menunjukkan bahwa efikasi diri merupakan prediktor terkuat terhadap minat berwirausaha. Lingkungan keluarga membentuk efikasi diri dan minat berwirausaha secara signifikan. Pendidikan kewirausahaan terbukti meningkatkan efikasi diri secara nyata, namun pengaruh langsungnya terhadap minat berwirausaha tetap tidak signifikan. Pelajaran penting yang muncul dari hasil ini adalah bahwa penguasaan konten akademik saja tidak akan berubah menjadi tindakan karier kecuali jika efikasi diri meningkat secara substansial. Bagi universitas, temuan ini memberikan sinyal perlunya merancang ulang kurikulum agar tidak hanya berfokus pada penguasaan teoretis, tetapi juga secara aktif membangun kekuatan psikologis dan memperkuat hubungan antara pembelajaran di kelas dengan dukungan keluarga.